The flower of paradise : Marian devotion and secular song in medieval and renaissance music - Rothenberg, David J. (David Joseph) (Oxford University Press, 2011)
There is a striking similarity between Marian devotional songs and secular love songs of the late Middle Ages and Renaissance. Two disparate genres-one sacred, the other secular; one Latin, the other vernacular-both praise an idealized, impossibly virtuous woman. Each does so through highly stylized derivations of traditional medieval song forms-Marian prayer derived from earlier Gregorian chant, and love songs and lyrics from medieval courtly song. Yet despite their obvious similarities, the two musical and poetic traditions have rarely been studied together. Author David J. Rothenberg takes.